How COVID-19 pandemic affect nutritional status - Pittara Pansawira (World Nutrition Journal, 2021)
In Indonesia, COVID-19 has primarily affected food access and causes drop of income. The poor and vulnerable groups have difficulties in affording high nutritional value food thus resulting in, not only decline of food intake, but also lower dietary quality.4